Institutional adjustment of young adults undergoing forensic assessment - Hilton, N. Zoe (Psychology, crime & law, 2021)
Adolescence and emerging adulthood are considered distinct developmental periods and times of peak criminal offending and onset of many major mental disorders. Previous research suggests that adolescents and young adults in adult correctional institutions adjust more poorly than their older counterparts do, and psychosocial adjustment is associated with pre-existing vulnerability. Research with institutionalized young adults is sparse. We studied institutional and psychosocial adjustment of men admitted to a forensic psychiatric hospital. Overall, younger age on admission was associated with previous vulnerability (i.e. adverse childhood experiences) and institutional adjustment (e.g. assaults, management problems), but not psychosocial adjustment (i.e. mood problems, psychosis, social withdrawal). Age had small and inconsistent effects on adjustment measures in regression analyses controlling for length of stay. Comparing the 141 young adults aged 18-24 with 141 men aged 25-59 matched on pre-admission psychiatric and criminal history did not yield age-related group differences. The apparent poorer adjustment of young adults may be attributable to younger onset of psychiatric and criminal justice involvement, resulting in earlier admission to the institution.